Efficacy and Safety of Rivaroxaban and Enoxaparin for Thromboprophylaxis Among Total Hip Arthroplasty Patients: A Systematic Review and Meta-Analysis - Wang, Chong; Lan, Shuhua; Xie, Panpan; Yang, Ruifeng (The Journal of Hip Surgery, 2024)
Background Venous thromboembolism (VTE) is one of the major and potentially life-threatening complications following major orthopedic surgeries. Research evidence comparing the effectiveness of rivaroxaban and enoxaparin for thromboprophylaxis specific to total hip arthroplasty (THA) has been limited. Hence, this review was done to compare the efficacy and safety of rivaroxaban against enoxaparin for thromboprophylaxis after THA.Materials and Methods We conducted a search in databases including Medline, EMBASE, ScienceDirect, Google Scholar, and Cochrane Library from inception until May 2021. Randomized controlled trials directly comparing the effectiveness of rivaroxaban and enoxaparin for thromboprophylaxis among patients undergoing THA were eligible for inclusion. Outcome parameters assessed were efficacy in terms of total VTE and all-cause mortality, major VTE, deep vein thrombosis, symptomatic VTE, and safety in terms of major bleeding events, clinically relevant nonmajor bleeding events, minor bleeding events, total bleeding events, drug-related adverse events, and wound infection. We performed a meta-analysis with a random effects model and reported a pooled risk ratio (RR) with a 95% confidence interval (CI).Results Eleven studies, including 9057 participants, were analyzed. Amongst efficacy outcomes, VTE and all-cause mortality pooled an RR of 0.58 (95% CI: 0.34–0.99), major VTE pooled an RR of 0.37 (95% CI: 0.15–0.90), deep vein thrombosis pooled an RR of 0.57 (95% CI: 0.32–1.02), and symptomatic VTE pooled an RR of 0.51 (95% CI: 0.30–0.87). Amongst safety outcomes, major bleeding events pooled an RR of 1.18 (95% CI: 0.77–1.80), total bleeding events pooled an RR of 1.12 (95% CI: 0.93–1.34), drug-related adverse event pooled an RR of 0.99 (95% CI: 0.87–1.12), and wound infection pooled an RR of 1.11 (95% CI: 0.58–2.14).Conclusion Rivaroxaban is a more efficacious drug in terms of VTE and all-cause mortality compared to enoxaparin following THA, and rivaroxaban was non-inferior in terms of safety profiles such as wound infection, bleeding, and drug-related adverse events.
Keywords: Enoxaparin; Rivaroxaban; meta-analysis; total hip arthroplasty